Drug-Loaded Microbubbles Combined with Ultrasound for Thrombolysis and Malignant Tumor Therapy. (1st October 2019) - Gong, Qian; Gao, Xingxing; Liu, Wenfang; Hong, Tingting; Chen, Chuanpin
Abstract : Cardiac-cerebral thrombosis and malignant tumor endanger the safety of human life seriously. Traditional chemotherapy drugs have side effects which restrict their applications. Drug-loaded microbubbles can be destroyed by ultrasound irradiation at the focus position and be used for thrombolysis and tumor therapy. Compared with traditional drug treatment, the drug-loaded microbubbles can be excited by ultrasound and release drugs to lesion sites, increasing the local drug concentration and the exposure dose to nonfocal regions, thus reducing the cytotoxicity and side effects of drugs. This article reviews the applications of drug-loaded microbubbles combined with ultrasound for thrombolysis and tumor therapy. We focus on highlighting the advantages of using this new technique for disease treatment and concluding with recommendations for future efforts on the applications of this technology.